Hydrodynamic and hydrochemical conditions in the hyporheic zone of a heavily anthropogenically transformed river in the Konstantynów Łódzki area (Poland) - Krogulec, Ewa; Małecki, Jerzy J.; Szostakiewicz-Hołownia, Marzena; Trzeciak, Joanna; Zabłocki, Sebastian; Ziułkiewicz, Maciej (Quaestiones Geographicae, 2025)
The historical Ner River, receiving sewage for 150 years, has undergone significant hydrochemical changes. Natural hydrological conditions have also been substantially altered due to increased flood dynamics resulting from inflows from the sewered catchment area, which covers a significant portion of the Łódź agglomeration. Research conducted on the Ner River in the Konstantynów Łódzki area aimed to characterise the current hydrodynamic and hydrochemical conditions within the river valley, specifically focussing on its hyporheic zone (HZ). This study was conducted across three research profiles located approximately 5 km downstream from the discharge point of treated sewage from the Group Wastewater Treatment Plant in Łódź. Hydraulic conductivity measurements of riverbed formations indicate moderate to high permeability, facilitating substantial exchange between river water and groundwater due to the large morphological river bottom features. This was supported by vertical hydraulic gradient measurements, indicating predominant groundwater discharge within the profiles. Water samples collected from the riverbed exhibited diverse physicochemical features and chemical compositions. Metal content in the riverbed sediments of the Ner River decreased with increasing distance from the sewage discharge point. The HZ demonstrates the capability to mitigate natural disturbances, process nutrients and stabilise metals. Nevertheless, anthropogenic pressures disrupt the natural hydrological regime, chemical activities and biological processes. The study underscores the necessity of correlating chemical composition results with model estimates of upwelling or downwelling volumes for a comprehensive understanding of hydrochemical changes within heavily anthropogenically transformed river HZs. Furthermore, this correlation facilitates a reliable evaluation of hydrochemical variations within the HZ.